ANALYSIS OF COASTAL WATER QUALITY AT MARINE TOURISM SITES IN THE CITY OF SIBOLGA - Sihombing, Kelvin; Harahap, R. Hamdani; Mulya, Miswar Budi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2023)
Sibolga is one of the cities in North Sumatra Province that has outstanding marine tourism destinations, some of which include Pelabuhan Lama (Anggar) Beach and Ujung Sibolga Beach. This research aims to analyze the coastal water quality of marine tourism objects in Sibolga City. This research was conducted from March to July 2023 at Pelabuhan Lama (Anggar) and Ujung Sibolga Beach. Water quality assessment is carried out using the STORET method. Pelabuhan Lama (Anggar) Beach obtained a total score of -18, and Ujung Sibolga Beach received a total score of -26. The total scores for both tourist sites fall into class C with a moderate pollution category.